Cytogenetic studies on three tenebrionid beetles, Tenebrio molitor, Alphitobius diaperinus and Zophobas morio (Coleoptera: Tenebrionidae): An overview and new data - Mora, Pablo; Rico-Porras, José M.; Palomeque, Teresa; Valdivia, Ana; Cabral-De-Mello, Diogo C. [UNESP]; Lorite, Pedro (Biology Centre, AS CR, 2024)
Here, a comprehensive cytogenetic analysis of three species of tenebrionid beetles: Alphitobius diaperinus, Tenebrio molitor and Zophobas morio, is presented. This paper also contains a review of the cytogenetic information for each species and adds new data. The male karyotype of both T. molitor and Z. morio is 2n = 18 + Xyp, with large heterochromatic blocks in the pericentromeric regions of all chromosomes. The male A. diaperinus karyotype is 2n = 18 + X0, also with heterochromatic pericentromeric regions in all chromosomes. The location of the nucleolar organizer regions (NORs) differs in each species: in A. diaperinus, it is located on the smallest pair of autosomes, while in T. molitor, it is on two pairs of autosomes and both sex chromosomes. In contrast, it is exclusively located on the X chromosome in Z. morio. Telomere analysis revealed that all species have TCAGG repeats in their telomeres, but lack the canonical TTAGG insect telomeric motif. In addition, a study of the distribution of satellite DNA and composition revealed that each species has a main satellite DNA family forming the pericentromeric heterochromatin. Fluorescence in situ hybridization of each of these satellites did not produce hybridization signal in the other two species, indicating a divergence in repetitive DNA composition among them. This study adds to the understanding of chromosomal organization, heterochromatin distribution and repetitive DNA dynamics in tenebrionid beetles and sheds light on their cytogenetic diversity and evolutionary significance.
Keywords: C-banding; fluorescence in situ hybridization; Karyotype; NOR; satellite DNA; telomere